The Pengaruh Flash Sale dan Fear of Missing Out terhadap Impulse Buying Blind Box Nommi Miniso dimediasi Perceived Value - Ginting, Jepindonta Arnades; Harjanti, Sri (JURNAL MANAJEMEN MOTIVASI, 2026)
This study analyzes the effects of flash sales and fear of missing out (FoMO) on impulse buying, with perceived value as a mediating variable among Nommi Miniso Blind Box consumers on Shopee. Using a quantitative approach, data were collected via surveys from 230 respondents in Yogyakarta through purposive sampling. Partial Least Squares (PLS) analysis via SmartPLS 4.0 was applied. Results show flash sales and FoMO significantly influence impulse buying and perceived value. While perceived value positively affects impulse buying, it does not significantly mediate the relationship. Emotional triggers and time pressure primarily drive impulsive purchases of collectible e-commerce products.